2008
DOI: 10.1038/jhh.2008.40
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the metabolic syndrome on the predictive values of new risk markers in the general population

Abstract: Although the metabolic syndrome (MetS) is positively associated with high-sensitivity C-reactive protein (hsCRP), negatively associated with N-terminal probrain natriuretic peptide (Nt-proBNP) and inconsequently related to urine albumin/creatinine ratio (UACR) they are all associated with cardiovascular events. Therefore, we wanted to determine the influence of MetS on the predictive values of UACR, hsCRP and Nt-proBNP. On the basis of the definition of MetS by the International Diabetes Federation, a Danish p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The detrimental impact of an abrupt period of physical inactivity on glycemic control and integrated rates of MPS was associated with elevated concentrations of inflammatory markers. Our study represents a relevant clinical observation showing that prediabetic older persons are susceptible to inactivityinduced worsening of an insulin-resistant phenotype, as is observed in healthy older and younger persons (14)(15)(16)(17). Uniquely, we show that the reversal of this phenotype, which occurs in younger adults (14), is impaired on return to normal activity in our population.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The detrimental impact of an abrupt period of physical inactivity on glycemic control and integrated rates of MPS was associated with elevated concentrations of inflammatory markers. Our study represents a relevant clinical observation showing that prediabetic older persons are susceptible to inactivityinduced worsening of an insulin-resistant phenotype, as is observed in healthy older and younger persons (14)(15)(16)(17). Uniquely, we show that the reversal of this phenotype, which occurs in younger adults (14), is impaired on return to normal activity in our population.…”
Section: Discussionsupporting
confidence: 68%
“…For instance, hospitalized elderly individuals take only ~650-1,000 steps•d −1 (12) as do older persons convalescing from illness or surgery (13). Studies have shown that such periods of acute inactivity result in the onset of insulin resistance in younger adults (14)(15)(16)(17) but that younger persons recover with a return to daily ambulation (14). To our knowledge, only two studies (18,19) have examined how physical inactivity (daily step reduction [SR]) mimicking hospitalization (12), affects muscle metabolic function in older adults.…”
mentioning
confidence: 99%
“…Nonetheless, based on previous studies (18,19,76) addressing hsCRP, this biomarker has been considered for adoption into risk assessment algorithms (77). Recently conducted studies have, however, shown that the predictivity of hsCRP is attenuated when tested in a multivariable model in the general population (78), and together with natriuretic peptides in patients with known CAD (79)(80)(81)(82). In our study, hsCRP appears to be a potential predictor for all-cause mortality, also when adjusted for BNP, but does not reflect cardiac strength of our study is the absence of patients lost to follow-up; in fact, there were only four patients with no measurements available for hsCRP.…”
Section: Papermentioning
confidence: 99%